Lumbar Fixation Using the Cortical Bone Trajectory Fixation: A Single Surgeon's Experience With 3-Year Follow-up. Issue 3 (31st March 2022) - Arzoglou, Vasileios; Vial, Izziddine; Hussain, Masood; Deepak, Srihari; Andalib, Amin; Storey, Matthew; Graham, Christopher; Tsitlakidis, Abraham
Abstract : BACKGROUND: Pedicle screw fixation with a cortical bone trajectory (CBT) has emerged as an effective alternative to traditional techniques of lumbar fusion, especially in osteoporotic patients. The proposed benefits of CBT screws include a stronger grip in the elderly and osteoporotic population and low surgical morbidity. We present a prospective study with a 3-yr follow-up of 80 patients operated on by the same surgeon. OBJECTIVE: To assess the outcomes of the CBT technique in patients with at least 3-yr follow-up. METHODS: Eighty patients who underwent lumbar fusion using the CBT fixation by the same surgeon were included in the study. The outcomes, Oswestry Disability Index (ODI), back pain visual analog scale (VAS), leg pain VAS, walking distance, opioid use, nonopioid analgesia use, and EuroQol 5D-5L index were measured preoperatively and during the 1- and 3-yr postoperative follow-up visits. Time from surgery, indication for surgery, intervertebral cage insertion, body mass index (BMI), and their interactions were analyzed as predictors in a separate mixed-effects model for each outcome. We assessed all outcomes as 1 group of patients, but we also elaborated on a classification scheme based on a combination of radiological and dynamical assessment of microinstability, macroinstability, and spondylolisthesis. RESULTS: The relationship between the outcomes and time showed considerable interpatient heterogeneity because all intercepts (all P < .001) and the linear trend temporal slopes for walking distance ( P = .019) and nonopioid analgesics use ( P < .001) varied across patients. The intercepts and the linear trend slopes for nonopioid use were significantly correlated ( P = .039). Time from surgery significantly predicted all outcomes ( P < .001). Intervertebral cage insertion was associated with significantly less opioid use ( P = .017). The indication for surgery significantly modified the effect of time on the ODI ( P = .042) and the VAS for leg pain ( P = .025). Moreover, higher BMI was also associated with a significantly steeper linear trend in the VAS for leg pain ( P = .028). Among patients with microinstability, the linear trend for the EuroQol 5D-5L index was significantly steeper with, rather than without, spondylolisthesis ( P = .024). CONCLUSION: In all patients who underwent CBT-based lumbar fusion, there was a steep trend toward improvement in ODI, VAS score for leg pain, and opioid use at 1 yr after surgery. Patients with normal BMI and microinstability alone had a decline in the rate of improvement at 3 yr, whereas the rest continued to show improvement at 3 yr postprocedure. Spinal fixation and fusion using CBT shows satisfactory outcomes. Larger series and a double-blind randomized trial would be helpful for further identifying the pros and cons of this technique.